Dampak Pengambilan Keputusan Pemerintah Terkait Pemindahan Ibu Kota Negara Dalam Aspek Geografi, Sosial Politik, Dan Ekonomi - Sriyono, Sriyono; Rahmayani, Aprilia; Wahidah, Zahrotul (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
This research comes from a phenomenon that has been hot in the news recently. It has been announced that the capital city of Indonesia will be moved to the East Kalimantan region. Before the capital city is moved, the government needs to consider the area that will be called the new national capital later. These considerations include the geographical, socio-political and economic aspects of the Kalimantan region which will have an impact on the development of Indonesia. The main reason for moving the country's capital was to improve the Indonesian economy. Therefore, this research was prepared to explain how the government makes decisions regarding the relocation of the country's capital by considering aspects such as geography, socio-political and economic aspects as well as the impacts of these decisions. This research uses a literature review methodology. Based on research from several literatures, it can be concluded that the government's decision regarding moving the country's capital by looking at geographical, socio-political and economic aspects will have a good impact on the country, especially on the economy.